History matters : patriarchy and the challenge of feminism - Bennett, Judith M. (University of Pennsylvania Press, 2006)
"Written for everyone interested in women's and gender history, History Matters reaffirms the importance to feminist theory and activism of long-term historical perspectives. Judith M. Bennett, who has been commenting on developments in women's and gender history since the 1980s, argues that the achievement of a more feminist future relies on a rich, plausible, and well-informed knowledge of the past, and she asks her readers to consider what sorts of feminist history can best advance the struggles of the twenty-first century."--Jacket